Cultural heritage incentives for the conservation of traditional settlements: The case of Malaysia, Japan and South Korea / Indera Syahrul Mat Radzuan - Indera Syahrul, Mat Radzuan (2016)

(untitled)
A variety of incentives mechanisms have been formulated by many countries in order to promote the conservation of their cultural heritage, specifically in preserving their distinctive traditional villages. However, the existence of these traditional villages in the contemporary landscape has been considered fragile thus as many of them have been torn down due to rapid urbanization. This research examine the conservation efforts initiated by the Japanese, Korean and Malaysian authorities in safeguarding their historic villages ranging from tangible to intangible heritage. As observed, there has been little or no research into the nature and impact of these incentives and how they might be integrated into heritage management strategies. Apart from that, scholars have criticized the so-called incentives policies due to their inability to provide equal and equitable distribution of benefits to the local residents within the effected village areas. This research seeks to investigate the various types of incentive policies that have been applied in Japan, South Korea and Malaysia. For these three Asian countries, this research is conducted to address the overarching question of whether incentives programme that have been formulated for the communities are suitable towards their aspirations and real needs. Reflecting on the differences of the policy provisions, this research has adopted a case study approach; where the mixed methods approaches were employed, including a questionnaire survey as a tool for data gathering coupled with indepth interviews. Formal interviews were carried out with the officials of national, state and local government in these countries. The case study assesses the communities and professionals view on the implementation of tangible and intangible heritage conservation programme. iv The research is the first insightful study of the historic villages which attempts to draw out the importance of the effectiveness of the incentives programme in guiding the conservation efforts for the local economic development. Despite numerous efforts to foster community engagement in the study areas, however, the pertinent issue is still overshadowing programme implementation – does the communities were given adequate recognition in the decision making process or community engagement is just another public relation exercise? Hence, this research has also identified constraints on the current incentives policy implementation and issues due to the rapid development and its impacts to local livelihood. Result shows there was a divergent direction between the current incentives policy and the local aspirations between sites. In most cases, the cultural heritage conservation has been found to be a catalyst to fulfil a heritage tourism advantage rather than to cater to the local community needs. Further investigations into this area seem to be necessary in order to offer a more sound and rounded guide to an effective incentives policy